(untitled) (American Journal of Islam and Society, 1992)
It is He Who made the sun a radiance, and the moon a light, and determined it by stations, that you might know the number of the years and the reckoning (of time) ... (Qur’an 10:5). Every community possesses a personality and certain traits that distinguish it from others. The ummah of Islam was blessed by Allah Most High with a distinctive personality so that it could serve as a community of the median way (wasatiyah) and as a witness (shahadah): "Thus We appointed you a mid-most nation, so that you might be witnesses over all mankind" (2:143). In view of the important civilizational role to be played by the Muslim ummah, Allah created the elements in its personality with great care in order to ensure that the expected results would come to fruition and that the ummah would become the best community ever brought forth: "You are the best nation ever brought forth to mankind" (3:110). Among the constituent elements of the ummah’s cultural and civilizattional identity is its perspective on time, be it past, present, or future, and how it is to be measured. The past consists of history, from which lessons are to be learned. The present is the current reality, every moment of which is to be used to the best advantage or invested. The future is that which is anticipated and planned for so that it may become more resplendent. The communities that went before Islam both understood and calculated time in order to achieve their goals and build their civilizations. To differing degrees, all of them were successful in their endeavor to mark the passage of time. However, every system they devised suffered from calendars featuring ten months in a year, others with widely varying numbers of days in a month, calendars that began in the spring while others ...